Hubungan Pengetahuan Perawat Tentang Proses Keperawatan Dengan Pendokumentasian Asuhan Keperawatan Di Ruang Rawat Inap RSUD Majalaya - Deni Arisandi; Asep Solihat (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Nursing care are an integral part of health care. The task of the nurse in providing nursing care, among others, assess the needs of patients, nursing action plan, implement the plan of action, evaluate the results of nursing care given and documenting nursing care. The low quality of the completeness of the documentation of nursing care becomes one of the problems in government and private hospitals. Preliminary studies in Majalaya hospital show documentation of nursing care has not been standardized. Documentation of nursing care is an essential element in the accountability of nurses. Documentation must be in accordance with the nursing process. This research was conducted in the inpatient Majalaya hospital in June-August 2022. This study is a descriptive correlation with cross-sectional design. The population was a nurse working in the hospital inpatient Majalaya. Sampling technique was the total number of sampling with 48 nurses. The research instrument used questionnaires to assess nurses' knowledge of the nursing process and observation sheets to determine the completeness of the documentation of nursing care. The results showed the majority of respondents (72.9%) good knowledge of the nursing process, nearly half of respondents (27.1%) knowledgeable enough, and none (0%) less knowledgeable. Documents nursing care the majority (52.1%) filled completely only 47.9% were incomplete. The results obtained Kendalltau bivariate analysis with correlation coefficient 0.635 with a significance level of 0.002 <α (0.05) thus concluded that there is a significant relationship between nurses' knowledge of the nursing process with documentation of nursing care. It is recommended that the training hospitals Majalaya conduct education and training on the nursing process, as well as continuous supervision of at least 3 months by the head of the room in order to improve the implementation of nursing care documentation